MANAJEMEN LATIHAN EKSTRAKURIKULER OLAHRAGA UNTUK MENINGKATKAN PRESTASI NON AKADEMIK SISWA (Studi Deskriptif Kualitatif di SDN Pasirhuni 01 Kecamatan Cimaung, Kabupaten Bandung) - Yoseptry, Ricky; Basin, Basin; Audah, Irfan; Rahman, Rita; Marlianty, Risni (STKIP PGRI Situbondo, 2025)
This study aims to describe and analyze the management of extracurricular sports training at SDN Pasirhuni 01, Bandung Regency and its influence on improving students' non-academic achievements in sports. Extracurricular sports have an important role in developing students' potential outside of academics, including improving achievements in various sports. Effective training management is expected to optimize students' potential and produce proud achievements. The research method used is descriptive qualitative. Data were collected through observation, in-depth interviews with sports teachers, students participating in extracurricular activities, and related school parties, as well as documentation of training programs and student achievement records. Data analysis was carried out qualitatively through data reduction, data presentation, and drawing conclusions. The results showed that the management of extracurricular sports training at SDN Pasirhuni 01 involved planning a training program that included selecting sports, preparing schedules, and determining training objectives. This study concludes that planned and structured extracurricular sports training management has a positive contribution to improving students' non-academic achievements at SDN Pasirhuni 01, Bandung Regency. Schools are expected to continue to support and develop extracurricular sports programs as a forum for developing student potential holistically.